Effect of reduced exposed surface area and enhanced infiltration on ammonia emission from untreated and separated cattle slurry. (November 2021) - Pedersen, Johanna; Nyord, Tavs; Feilberg, Anders; Labouriau, Rodrigo; Hunt, Derek; Bittman, Shabtai
Abstract : Ammonia (NH3 ) loss during field application of liquid manure (slurry) causes loss of nutrients for the crops and contributes to contamination of the environment. The emission can be mitigated by different low-emission application technologies and slurry treatment prior to application. It is assumed that a reduced area for air-slurry interaction will reduce the emission. The NH3 emission mitigation potential of technologies intended to reduce manure-air contact by reducing the exposed surface area (ESA) of the slurry or enhancing slurry infiltration was investigated for cattle slurry applied on grassland. Treatments tested were: 1) removing solids by solid–liquid separation of the slurry, 2) reduced ESA by narrow band application, and 3) application with a sub-surface-deposition (SSD) slurry application (creating aeration slots). For untreated cattle slurry NH3 emission was not reduced by reducing ESA, but application over aeration slots significantly decreased emission. However, reduced ESA by band application reduced emission from separated slurry compared to broadcast applied slurry, but no additional reduction was obtained by using the SSD technique. Lower emission was generally observed from separated slurry compared to untreated slurry for all application methods. This study shows that a reduction in NH3 emission is not necessarily obtained solely by reducing the ESA. It is hypothesized that rapid surface drying or crust formation of the untreated slurry in the relatively warm sunny conditions of these trials mitigated NH3 emission, thereby masking the effects of a reduced ESA. Highlights: Surface crust formation can counteract NH3 emission increases at high temperatures. Reduced mitigating effect of lowering ESA on NH3 emission under warm conditions. Enhanced infiltration by separation of cattle slurry reduced NH3 emission.